SPSS analysis for predicting the occupational health and safety of sawmill workers in the wood processing industries in Kerala, India - Narayan, Prasanth; Arutchelvan, V.; Jacob, Susan; Warimani, Mahammadsalman; Khan, Sher Afghan; Sonachalam, M.; Shekar, Chandra; Majdi, Ali; Algburi, Sameer; Ali, Abduljabar H.; Khan, Wahaj Ahmad; Naik, N Channa Keshava (Springer, 2025)
This study examines how the occupational health of sawmill workers in Kerala, India, is affected by dust exposure and equipment noise, with a particular emphasis on lung function and noise-induced hearing loss (NIHL). One-way analysis of variance and Scheffé post hoc multiple comparisons were utilized to analyze the data using SPSS Version 26. Measurements were taken for key lung function parameters—forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and the ratio of FEV1 to FVC (FEV1/FVC)—along with hearing threshold levels (HTL) at frequencies from 250 to 8000 Hz. The findings indicated statistically significant differences (P < 0.05) in lung function indices and HTL across different noise exposure levels, except for the profound noise exposure group (G5). Notably, workers exhibited a greater propensity to expose their right ear to noise sources, suggesting a behavioral factor in NIHL. Additionally, noise interference from multiple simultaneously Operating machines was identified as contributing to hearing loss. These results demonstrate the urgent need for improved workplace safety measures, including efficient dust management, the use of personal protective equipment (PPE), routine health examinations, and comprehensive training programs for workers. By implementing these strategies, occupational health hazards can be significantly reduced, thereby enhancing the overall health and safety of sawmill workers.